Upgrading and fixing PC's for dummies - Rathbone, Andy (South Lake : IDG Books Worldwide, 1995)
Part I. Biting Your Fingernails -- II. The PC Parts You Can See (Peripherals) -- III. The Stuff Hiding Inside Your PC -- IV. Telling your Computer What you' ve Done -- V. The part of Tens.
Part I. Biting your fingernails --II. The PC parts you can see (peripherals) --III. The stuff hiding inside your PC --IV. Telling your computer what you've done --V. The part of tens.
Include index